PENGEMBANGAN BAHAN AJAR MENULIS TEKS PROSEDUR BERBASIS KEARIFAN LOKAL DENGAN PENDEKATAN SCIENCE, TECHNOLOGY, ENGINEERING, ART, AND MATHEMATICS (STEAM) PADA KELAS VII MTs - INDRIYATI, SRI; KUNTORO, KUNTORO; SUROSO, EKO; SUKIRNO, SUKIRNO (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This study is research that develops teaching materials for learning to write procedural texts based on local wisdom using the Science, Technology, Engineering, Art, and Mathematics (STEAM) approach for seventh-grade students at MTs. The development of these teaching materials is an effort to innovate conventional teaching materials that have been used so far. This research aims to: (1) determine the needs of students and teachers in preparing teaching materials for writing procedural texts based on local wisdom using the STEAM approach, (2) produce the development of teaching materials for writing procedural texts based on local wisdom using the STEAM approach, (3) produce teaching materials for writing procedural texts based on local wisdom using the STEAM approach that are valid and will be used in learning at MTs, and (4) improve the effectiveness of learning outcomes for seventh-grade students at MTs through the use of teaching materials for writing procedural texts based on local wisdom using the STEAM approach. This research uses the Research and Development (R&D) method with the stages of the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) as follows: (1) Potential and Problems, (2) Data Collection, (3) Product Design, (4) Product Validation, (5) Product Revision, (6) Product Testing, and (7) Data Analysis and Reporting. Data collection in this study used interviews and questionnaires. The research instruments used were: (1) student needs questionnaire, (2) teacher needs questionnaire, (3) validation test questionnaire. The results of this study produced the development of teaching materials for writing procedural texts based on local wisdom using the STEAM approach, with a material and media validity level ranging from 90.01% to 100.00%, and the product validity level was very feasible. Based on this analysis, it can be concluded that there is a strong need for teaching materials for writing procedural texts based on local wisdom using the STEAM approach. The development of good teaching materials can serve as a model for teachers to carry out higher-quality learning. The teaching materials produced add to the reference of teaching materials that are feasible to be tested and further developed. ABSTRAKPenelitian ini adalah penelitian yang mengembangkan bahan ajar untuk pembelajaran menulis teks prosedur berbasis kearifan lokal dengan pendekatan Science, Technology, Engineering, Art, and Mathematics pada kelas VII MTs. Pengembangan bahan ajar merupakan upaya memberikan inovasi pada bahan ajar konvensional yang selama ini digunakan. Penelitian ini bertujuan untuk: (1) mengetahui kebutuhan peserta didik dan guru dalam penyusunan bahan ajar menulis teks prosedur berbasis kearifan lokal dengan pendekatan STEAM, (2) menghasilkan produk pengembangan bahan ajar menulis teks prosedur berbasis kearifan lokal dengan pendekatan STEAM, (3) menghasilkan bahan ajar menulis teks prosedur berbasis kearifan lokal dengan pendekatan STEAM yang valid dan akan digunakan dalam pembelajaran di MTs, dan (4) meningkatkan keefektifan hasil belajar peserta didik kelas VII MTs melalui penggunaan bahan ajar menulis teks prosedur berbasis kearifan lokal dengan pendekatan STEAM. Penelitian ini menggunakan metode Research and Development (R&D) dengan tahapan penelitian model ADDIE (Analysis, Design, Development, Implementation, Evaluation) sebagai berikut: (1) Potensi dan Masalah, (2) Pengumpulan Data, (3) Desain produk, (4) Validasi Produk, (5) Revisi Produk, (6) Uji Coba Produk, dan (7) Analisis Data dan Pelaporan. Pengumpulan data dalam penelitian ini menggunakan wawancara dan angket. Intrumen penelitian yang digunakan, yaitu (1) angket kebutuhan siswa, (2) angket kebutuhan guru,( 3) angket uji validasi. Hasil penelitian ini menghasilkan pengembangan bahan ajar menulis teks prosedur berbasis kearifan lokal dengan pendekatan STEAM, tingkat validitas materi dan media pada rentang 90,01% - 100,00% serta tingkat validitas produk sangat layak. Berdasarkan analisis tersebut dapat disimpulkan kebutuhan akan bahan ajar menulis teks prosedur berbasis kearifan lokal dengan pendekatan STEAM sangat dibutuhkan. Pengembangan bahan ajar yang baik dapat menjadi model bagi guru untuk melaksanakan pembelajaran yang lebih berkualitas. Bahan ajar yang dihasilkan menambah referensi bahan ajar yang layak untuk diujicobakan serta dikembangkan lebih lanjut.